1992
DOI: 10.1037/0097-7403.18.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Responding to a conditioned stimulus depends on the current associative status of other cues present during training of that specific stimulus.

Abstract: The comparator hypothesis is a response rule stating that responding to a Pavlovian conditioned stimulus (CS) reflects the associative strength of the CS relative to that of other cues (comparator stimuli) that were present during CS training. Thus, modulation of the associative strength of a CS's comparator stimulus should alter responding to that CS. These studies examined the stimulus specificity of this effect using within-subjects designs. Rats were trained on 2 CSs, each with a unique comparator stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 17 publications
2
39
0
Order By: Relevance
“…Our demonstrations of the mediated-extinction effect in Experiment 1 made use of a simultaneous AX compound in the first phase of training and led us to conclude that this effect would be likely to obscure any recovery-from-overshadowing effect under these training conditions. But, as we have already noted, Miller et al (1992) have successfully obtained the latter effect using just such a training procedure. We must assume that there is some other factor at work in the experiments by Miller and his colleagues that tips the balance in favour of recovery from overshadowing, but we have no notion at this stage as to what this factor might be.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our demonstrations of the mediated-extinction effect in Experiment 1 made use of a simultaneous AX compound in the first phase of training and led us to conclude that this effect would be likely to obscure any recovery-from-overshadowing effect under these training conditions. But, as we have already noted, Miller et al (1992) have successfully obtained the latter effect using just such a training procedure. We must assume that there is some other factor at work in the experiments by Miller and his colleagues that tips the balance in favour of recovery from overshadowing, but we have no notion at this stage as to what this factor might be.…”
Section: Discussionmentioning
confidence: 64%
“…A feature of the parameters used by Miller et al (1992) in their demonstration of recovery from overshadowing was that the target stimuli used on test (i.e., X and Y in the present notation) were intrinsically less effective at evoking conditioned suppression than were their associates (A and B). In contrast, previous work conducted in this laboratory indicated that the stimuli we used as X and Y were rather more salient than those used as A and B.…”
Section: Experiments 1bmentioning
confidence: 98%
“…According to the comparator hypothesis, these extinction trials should weaken Links 2 and 3 and, hence, the net overshadowing effect. Consistent with this prediction, several investigators (e.g., Cole, Oberling, & Miller, 1999;Kaufman & Bolles, 1981;Matzel, Schachtman, & Miller, 1985;Miller, Barnet, & Grahame, 1992) have found that posttraining extinction of the more salient (overshadowing) CS restored robust conditioned responding to the less salient (overshadowed) element of the stimulus compound (but see Holland, 1999;Rauhut, McPhee, & Ayres, 1998). According to the comparator hypothesis's account of overshadowing, if the associative strengths of Links 2 and 3 increase over reinforced trials according to a monotonic function, overshadowing should become more pronounced with extended compound training.…”
mentioning
confidence: 51%
“…Limited evidence for the specificity of comparator effects with respect to LI is seen in the present Experiment la, in which posttraining context extinction resulted in increased responding to the CS in Group LI-EXT, which had received the same CS during CS preexposure and the subsequent CS-strong US pairing, but not in Group C-EXT, which had received different CSs during CS preexposure and the subsequent CS-strong US pairing. More conclusive evidence for the specificity of comparator effects in general has heen seen in a variety of conditioning situations (e.g., conditioned inhibition, local context effects, and overshadowing) in a recent series of experiments by Miller, Barnet, and Grahame (1992).…”
Section: Methodsmentioning
confidence: 99%